PENERAPAN KEGIATAN TAHFIDZ DI TAMAN KANAK-KANAK SEMEN PADANG - Restha Ramadhani; Asdi Wirman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the uniqueness of the implementation of tahfidz activities at Semen Padang Kindergarten, which makes tahfidz one of the flagship programs in the field of Islam in accordance with its motto, namely "School with Natural and Islamic Nuances". The purpose of this study is to describe how the implementation of tahfidz activities at Semen Padang Kindergarten. This study uses a qualitative approach with descriptive methods. Informants in this study include the principal, teachers, and ustadz and ustadzah who are directly involved in tahfidz activities. Data were collected through observation, interviews, and documentation. Data analysis was carried out through four stages, namely data collection, data reduction, data presentation, and verification. The validity of the data was tested using triangulation techniques. The implementation of this tahfidz activity includes three main activities, namely planning, implementation, and assessment. Planning is made at the beginning of each semester with the school, the tahfidz institution, and parents before the start of the teaching and learning activities. The program is held every Monday through Thursday for one hour of study (8:00 AM to 9:00 AM WIB), divided into several activities: murojaah (recitation), ziyadah (recitation), individual talaqi (recitation), and collective talaqi (recitation). This activity has become a consistent morning routine and has a positive impact on the development of children's Quran memorization skills. Assessment of these activities is reflected in end-of-semester reports and students' achievements in various tahfidz competitions.